The effect of liver transplantation on patient‐centred outcomes: a propensity‐score matched analysis. (20th March 2019) - McLean, Kenneth A.; Drake, Thomas M.; Sgrò, Alessandro; Camilleri‐Brennan, Julian; Knight, Stephen R.; Ots, Riinu; Adair, Anya; Wigmore, Stephen J.; Harrison, Ewen M.
Summary: It is unclear whether liver transplantation confers an increase in health‐related quality of life (HR‐QoL) across all dimensions of health. This study aimed to estimate the effect of liver transplantation on HR‐QoL. Pre‐ and post‐transplantation patients attending an outpatient clinic were invited to complete the condition‐specific 'Short form of liver disease QOL' questionnaire. Mixed‐effect linear regression and propensity‐score matching (PSM) on pretransplantation characteristics were used to estimate the difference in overall HR‐QoL associated with transplantation. Of 454/609 (74.5%) eligible patients who were included in the analysis, 102 (22.5%) patients fall under pretransplantation category, and 352 (77.5%) were under post‐transplantation category. Overall HR‐QoL post‐transplantation significantly increased in patients without hepatocellular carcinoma (HCC) (β = 16.84, 95% CI: 13.33 to 20.35, P  < 0.001), but not with HCC (β = 1.25, 95% CI: −5.09 to 7.60, P  = 0.704). Donation after circulatory death (DCD) organ recipients had a significantly lower HR‐QoL (β = −4.61, 95% CI: −8.95 to −0.24, P  = 0.043). Following PSM, transplantation was associated with a significant increase in overall HR‐QoL (average treatment effect: 6.3, 95% CI: 2.1–10.9). There is a significant improvement in HR‐QoL attributable to transplantation in this cohort. Post‐transplantation HR‐QoL was affected by several factors, including HCC status and DCD transplantation, which has important implications for counselling prior to liver transplantation.